FAKTOR-FAKTOR YANG MEPENGARUHI KEBERHASILAN PELAKSANAAN PROGRAM PEREKAMAN E-KTP DIKABUPATEN ROKAN HULU - Putra, Doni Kesuma; Achnes, Sofia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Along with the development of information and communication technology is rapidlyincreasing this point is allowing the public to access any information they need in everydaylife, as if there is no limit. with the integration of technology and information systems alsohave an impact on public institutions such as local government. as well as identificationcards which initially Siak changed with e-ID card this is due to advances in technology andprevent people getting dual identity cards. E-ID card program launched by the InteriorMinistry of the republic of Indonesia in February 2011 in which the implementation isdivided into two stages. The first phase began in 2011 and ended on 30 April 2012 whichcovers 67 million people in 2348 dan197 districts districts / cities. While the second stagemencakup105 million inhabitants spread over 300 districts / city.And Rokan Hulu recordingstage 2, where Rokan Hulu successfully e-ID card recording to be the fastest in the e-ID cardrecording in Riau Province.The concept of the theory is that researchers use services, public policy and policyimplementation. theory of George C. Edward III in Sujianto ie variables that affect thesuccess of the implementation. while the research methodology is divided into: the location ofthe research is in population and civil registration offices Rokan Hulu, the type of researchthat is taking a qualitative approach with descriptive methods, informants, types and sourcesof data put on primary data and secondary data, and data collection techniques.From the above research will obtain results which are: communicasion is the delivery of policymakingto policy as well as implementing consistent carrying out an adequate polisy, information,and infrastructure, to support the operations of implementation of the policy. attitude/positive attitudethat earned from implementing a policy against a decision/policy are committed and consistent iscarrying out policies and not doing deskriminatif to the community. bureaucratic structure i.e. adetaild staff structure and clear to enable the policies that have been creted.Keywords: Implementation, Public policy. e-ID